2023
DOI: 10.3389/fonc.2023.1088000
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of COVID-19 on patients with cancer from areas of conflict within the MENA region treated at King Hussein Cancer Center

Abstract: BackgroundThere is a paucity of evidence regarding the impact of COVID-19 on cancer care among refugees or patients from areas of conflict. Cancer care for these populations remains fragmented due to resource scarcity and limited infrastructure.AimsTo explore the effect of COVID-19 on cancer care among patients from areas of conflict treated at King Hussein Cancer Center (KHCC).MethodologyWe performed a retrospective chart review of all patients from areas of conflict, treated at KHCC from 2018 to 2021. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Early strict restriction may have contributed to the reduction in hospital admissions in certain areas and led to increase in the rates of more advanced disease. [ 30 ] Many patients cancelled their appointments with their cancer doctors in the early phase of the pandemic. In one study from the region, 16% of the patients cancelled an appointment and 12% cancelled treatment sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Early strict restriction may have contributed to the reduction in hospital admissions in certain areas and led to increase in the rates of more advanced disease. [ 30 ] Many patients cancelled their appointments with their cancer doctors in the early phase of the pandemic. In one study from the region, 16% of the patients cancelled an appointment and 12% cancelled treatment sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, the recent Syrian crisis is considered by the United Nations to be the worst refugee catastrophe since the Second World War with more than 5 million displaced individuals across Jordan, Lebanon, and Turkey [ 4 ]. These populations from areas of conflict are confronted with considerable and complicated healthcare challenges that often create fertile grounds for the spread of infectious diseases and malnutrition among refugees [ 5 , 6 , 7 ]. In fact, studies have consistently shown that refugees have a higher burden of said diseases compared to their host populations [ 8 ].…”
Section: Introductionmentioning
confidence: 99%